Switched on to business. (20th December 2014) - Lambert, Alison
Abstract : Alison Lambert describes her career path as being unusual; however, she says, since all vets know that there's no such thing as an average day, why should there be an average way to get the best out of the valuable and varied skills that the veterinary qualification offers?